4‐Hydroxy‐benzoic acid (4‐diethylamino‐2‐hydroxy‐benzylidene)hydrazide: DFT, antioxidant, spectroscopic and molecular docking studies with BSA. (2nd September 2015) - Sharma, Vibha; Arora, Ekta Kundra; Cardoza, Savio
Abstract: The Schiff base 4‐hydroxy‐benzoic acid (4‐diethylamino‐2‐hydroxy‐benzylidene) hydrazide (SL) was synthesized and characterized. Its antioxidant activity was evaluated using 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) free radical scavenging action. Being a potent antioxidant its binding ability to the transport protein bovine serum albumin (BSA) was studied using fluorescence quenching and circular dichroism (CD) studies. The binding distance has been calculated by fluorescence resonance energy transfer (FRET) to be 1.85 Å and the Stern–Volmer quenching constant has been calculated to be (3.23 ± 0.45) × 10 5  M –1 . Quantum chemical analysis was carried out for the Schiff base using DFT with B3LYP and 6–311G** and related to the experimentally obtained results. For a deeper understanding of the mechanism of the interaction, the experimental data were complemented by protein–Schiff base docking calculations using Argus Lab. Copyright © 2015 John Wiley & Sons, Ltd.